2014
DOI: 10.1111/ped.12376
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of increases in interleukin‐6 and C‐reactive protein as predictors for white matter injury in preterm infants

Abstract: A combined elevation in serum IL-6 and CRP levels at birth was associated with the development of WMI in preterm infants with FIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…11 High levels of CRP and interleukin-6 at birth correlated with more white matter injury in preterm infants with foetal inflammatory response. 29 We found that grades III and IV haemorrhage, which are associated with spastic diplegia more strongly correlated with gestational age than with HCA. Although we found statistically significant outcomes in the HCA group with more bronchopulmonary dysplasia, retinopathy of prematurity, patent ductus arteriosus, early-onset sepsis and grade III/IV intraventricular haemorrhage in the HCA group, this disappears when corrected for gestational age.…”
Section: Discussionmentioning
confidence: 52%
“…11 High levels of CRP and interleukin-6 at birth correlated with more white matter injury in preterm infants with foetal inflammatory response. 29 We found that grades III and IV haemorrhage, which are associated with spastic diplegia more strongly correlated with gestational age than with HCA. Although we found statistically significant outcomes in the HCA group with more bronchopulmonary dysplasia, retinopathy of prematurity, patent ductus arteriosus, early-onset sepsis and grade III/IV intraventricular haemorrhage in the HCA group, this disappears when corrected for gestational age.…”
Section: Discussionmentioning
confidence: 52%
“…A body of research has suggested that prenatal infection and resultant fetal inflammatory response contribute to the pathogenesis of severe neonatal neurologic illness, such with white matter injury (WMI) [ 31 , 32 ], which in turn was associated with an increased risk of neurosensory impairment (hearing or vision) [ 33 , 34 ], and elevated blood CRP levels at birth were associated with WMI in preterm infants [ 35 ]. However, to date, no study has evaluated the direct relationship between immediate postnatal blood CRP levels (at or immediately after birth) and hearing status in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes may be related to early brain injury associated with high levels of systemic inflammation (Korzeniewski et al, ). Using markers of neurological impairment, including abnormalities on cranial ultrasound or magnetic resonance imaging or depressed electroencephalogram activity, some researchers have associated inflammation with brain injury in preterm infants (Inomata et al, ; Korzeniewski et al, ; Wikstrom, Ley, Hansen‐Pupp, Rosen, & Hellstrom‐Westas, ). Similarly, investigators have found associations between markers of neonatal inflammation and long‐term neurodevelopmental impairment, as measured by impaired behavioral, mental, and motor functioning (Kinjo et al, ; Korzeniewski et al, ; O'Shea et al, ).…”
Section: Neonatal Stress Embedding Modelmentioning
confidence: 99%